Novel plasma relativistic broadband source of high-power microwaves - Ernyleva, S.E.; Litvin, V.O.; Loza, O.T.; Bogdankevich, I.L. (Вопросы атомной науки и техники, 2013)
Numerical model of plasma-assisted microwave noise amplifier with 10% of energy efficiency on 150-MW power level is described. Pulse duration of 2 ns prevents the feedback in a 50-cm long device and provides generation of microwave pulses with continuous frequency control from 4 to 17 GHz and ≈ 2 GHz of a pulse bandwidth. Parameters of available electron beam sources are considered. Описана чисельна модель плазмового підсилювача шуму з ефективністю по енергії 10% на рівні потужності 150 МВт. Тривалість імпульсу 2 нс запобігає зворотний зв'язок в генераторі з довжиною 50 см і забезпечує генерацію СВЧ-імпульсів з можливістю безперервної перебудови частоти НВЧ-імпульсів від 4 до 17 ГГц і шириною спектру кожного імпульсу ≈ 2 ГГц. Розглядаються параметри існуючих джерел електронних пучків. Описана численная модель плазменного усилителя шума с эффективностью по энергии 10% на уровне мощности 150 МВт. Длительность импульса 2 нс предотвращает обратную связь в генераторе с длиной 50 см и обеспечивает генерацию СВЧ-импульсов с возможностью непрерывной перестройки частоты СВЧ- импульсов от 4 до 17 ГГц и шириной спектра каждого импульса ≈ 2 ГГц. Рассматриваются параметры существующих источников электронных пучков.